(untitled) (Global Media Journal - German Edition, 2024)
This paper deals with those working on the digital frontline, namely journalists, researchers and investigators who view, evaluate, and potentially use digital content such as eyewitness media for their reporting. Viewing such content often means being exposed to gruesome or disturbing material of all types. This can take its toll on the mental wellbeing of investigators. The paper outlines existing research in the domain and provides tips and advice on how so-called vicarious or secondary trauma caused by working with user-generated content can be avoided, or at least kept to a minimum. It also points to the potential harm that can be done. Another aim is to give the topic more prominence and encourage further research in this field.